FACTORS AFFECTING THE BEHAVIOR OF STUDENTS OF FACULTY OF ECONOMICS OF UNIVERSITAS KLABAT IN MAKING DECISION OF PURCHASING INDOMIE CAKALANG PRODUCT - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 12 No.2, 2013 JBE UNKLAB, 2013)
This study aimed to determine which of the factors predicted influence purchasing decision of Indomie instant noodle product with cakalang flavor by 116 faculty of economic students of Universitas Klabat. The independent variables are limited to cultural, social, personality, and psychological factors. The research design used is causal method with multiple linear regression, which came to the conclusion that the purchasing decision instant noodle, Cakalang flavor in particular is significantly simultaneously affected by each cultural, social, personality, and psychological factors, but there are culture as well as psychology significantly and positively affects purchasing decision. Psychology factor is more dominan than culture factor. The implication for PT Indofood Sukses Makmur is to pay more attention to all the factors that significantly affect the purchasing decision, more specifically to pschology factor which items such practical, easy to obtain products in residential area, and the influence of advertising